Strategi Manajemen Risiko Keuangan Dalam Industri Kreatif: Perspektif Pelaku Usaha Berbasis Kearifan Lokal - Muhammad Wahyudin (https://journal.metanusantara.com/jenius/index.php/jem, 2024)
Creative industries based on local wisdom have a strategic role in the national economy, especially in creating jobs and increasing the competitiveness of local products. However, economic uncertainty, fluctuations in raw material prices, and limited access to capital are the main challenges in the financial management of business actors in this sector. Therefore, this study aims to analyse the financial risk management strategies implemented by local wisdom-based creative MSMEs to improve their business resilience. This research uses a qualitative approach with a case study method. Data were obtained through in-depth interviews and observations of MSME actors in the creative industry who rely on local resources. Data were analysed using thematic techniques to identify patterns of strategies applied in dealing with financial risks. The results show that MSME actors adopt various risk mitigation strategies, such as product diversification, utilisation of digital technology for marketing and financial transactions, and optimisation of local raw materials that are more stable and affordable. In addition, social capital such as community networks and gotong royong have been shown to play a role in enhancing business resilience. This study also highlights the importance of government policy support, including tax incentives and access to fintech-based capital, although there are still obstacles in its implementation.